2017
DOI: 10.12659/ajcr.905726
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Stenosis Following Single-Lung Transplantation Successfully Treated with Intravascular Ultrasound-Guided Angioplasty and Stent Placement

Abstract: Patient: Female, 60Final Diagnosis: Pulmonary vein stenosis following single lung transplantSymptoms: Dyspnea on exertion and dry coughMedication: —Clinical Procedure: Balloon angioplasty and stenting of the left common pulmonary veinSpecialty: CardiologyObjective:Unusual clinical courseBackground:Pulmonary vein stenosis (PVS) is a rare event following lung transplantation, but is a serious complication that requires prompt diagnosis and treatment.Case Report:We describe the case of a 60-year-old woman who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…There has been a total of 16 publications following 18 cases of PVS. This includes 10 case reports (3,5,(7)(8)(9)(10)(11)(12)(13)(14) and 6 retrospective studies (15)(16)(17)(18)(19)(20). These studies are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There has been a total of 16 publications following 18 cases of PVS. This includes 10 case reports (3,5,(7)(8)(9)(10)(11)(12)(13)(14) and 6 retrospective studies (15)(16)(17)(18)(19)(20). These studies are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the perioperative mortality rate of untreated PVS patients (1 of 2 patients, 50%) (9,17) with treated patients (2 of 17 patients, 11.8%) (3,5,7,8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), it is suggested that the risk of patient mortality may be decreased by timely diagnosis and appropriate intervention. Retransplantation or open surgical repair to relieve stenosis increases the patient's risk of death, while stent implantation with or without balloon dilation offers a less invasive treatment and seems to have been performed more in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Percutaneous angioplasty with or without vascular endoprothesis is usually successful, with low mortality and morbidity rates, for severe anastomotic stenosis of the pulmonary artery (55). In patients with complete venous obstruction, angioplasty with dilatation and endovascular stent placement may be useful (56), but, on occasion, re-transplantation or lobectomy may be required (57).…”
Section: Treatmentmentioning
confidence: 99%